PENERAPAN MODEL PROJECT BASED LEARNING UNTUK MENINGKATKAN SIKAP TANGGUNG JAWAB SISWA DIKELAS III MADRASAH IBTIDIYAH RAHMATULLAH THEHOK KOTA JAMBI - Suhadah, Nurul; Ahmad Sayuti Nainggolan; Tabroni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was inspired by the minimal responsibility shown by third-grade students at Madrasah Ibtidaiyah Rahmatullah Thehok in Jambi City, which was evident in their lack of engagement with assignments, adherence to classroom protocols, and ownership of their educational activities. The aim of this study was to analyze the application of the Project Based Learning (PjBL) approach to enhance students’ responsibility. The research adopted a Classroom Action Research (CAR) format that was conducted over two cycles. Each cycle included four phases: planning, execution, observation, and evaluation. The study participants were third graders from Madrasah Ibtidaiyah Rahmatullah Thehok in Jambi City. Data were gathered through methods such as observation, surveys, documentation, and assessments of learning performance. The analysis was performed using both descriptive quantitative and qualitative techniques, by contrasting the outcomes from every cycle. The results indicated that the use of the Project Based Learning model effectively boosted students’ sense of responsibility. This enhancement was shown through increased engagement in project work, improved teamwork skills, better discipline in fulfilling assignments, and a heightened sense of accountability for their tasks. Moreover, the application of this educational approach positively influenced students’ academic performance, as demonstrated by the rising percentage of learning mastery across each cycle. The educational process became more dynamic, cooperative, and centered on the students, leading to more meaningful learning encounters. Based on the results, it can be inferred that the Project Based Learning model effectively promotes the responsibility of third-grade students at Madrasah Ibtidaiyah Rahmatullah Thehok in Jambi City. Consequently, Project Based Learning can be regarded as a viable teaching model that not only nurtures students’ accountability but also enhances the overall quality of the educational process and outcomes in elementary school settings.